Experimental study on grouting reinforcement characteristics of groutable fault fracture zone in western mining area - Mingjin FAN; Juntao CHEN; Hailong GU; Daozeng TANG; Gang HAN; Shuqiang ZHANG; Guangqiang LI (Meikuang Anquan)
Grouting transformation of aquifer is the most direct and effective means to control sandstone water disasters in western mining areas. In order to explore the influence of different factors on the grouting reinforcement characteristics of groutable fault fracture zone in western mining area, we design groutability test, uniaxial compressive strength test and permeability test to study the influence law and results of different factors on groutability and grouting reinforcement effect under the premise of complete groutability. The results show that when the water cement ratio is 1.5∶1, the strength of grouting reinforcement has reached the standard of field application, and the impermeability effect is almost the same and good as that when the water cement ratio is 1∶1. When the curing age is 14 d, the strength of grouting reinforcement under the two conditions of water cement ratio of 1∶1 and 1.5∶1 reaches the standard of field application, and the impermeability effect is almost the same and good as that when the curing age is 28 d. According to the research conclusions and field practice, the slurry with a water-cement ratio of 1.5∶1 was selected and applied to the grouting project. After grouting, the water absorption rate of each borehole was not greater than the critical value of 0.01 L/(min·m·m), and the grouting amount decreased from an average of 1 317.81 t to an average of 80.2 t. The grouting effect is obvious and good, which provides a guarantee for the safe mining of the mine and the ecological protection of water resources in the western mining area.